2011
DOI: 10.4269/ajtmh.2011.10-0423
|View full text |Cite
|
Sign up to set email alerts
|

Antihelminthic Therapy and Antimony in Cutaneous Leishmaniasis: A Randomized, Double-Blind, Placebo-Controlled Trial in Patients Co-Infected with Helminths and Leishmania braziliensis

Abstract: Helminth infections influence the clinical response to certain diseases and are associated with delayed healing time of patients with cutaneous leishmaniasis (CL) caused by Leishmania braziliensis. We conducted a randomized, double-blind, placebo-controlled clinical trial to examine the role of early versus deferred treatment of intestinal helminth infection on the clinical course of patients with CL treated with pentavalent antimony. (Clinicaltrials.gov number NCT00469495). A total of 90 patients were enrolle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 19 publications
1
30
0
2
Order By: Relevance
“…Al-though there was no statistically significant difference, patients who received early anthelmintic treatment took longer to heal their lesions than patients in the untreated group. This study shows that the early introduction of anthelmintic therapy does not improve clinical out-comes in patients coinfected with helminths and L. braziliensis (Newlove et al, 2011). A recent study showed that patients coinfected with intestinal helminths and Leishmania braziliensis had a higher frequency of tegumentary lesions and took longer to heal compared to patients without helminth infection (Azeredo-Coutinho et al, 2016).…”
Section: Introductionmentioning
confidence: 77%
“…Al-though there was no statistically significant difference, patients who received early anthelmintic treatment took longer to heal their lesions than patients in the untreated group. This study shows that the early introduction of anthelmintic therapy does not improve clinical out-comes in patients coinfected with helminths and L. braziliensis (Newlove et al, 2011). A recent study showed that patients coinfected with intestinal helminths and Leishmania braziliensis had a higher frequency of tegumentary lesions and took longer to heal compared to patients without helminth infection (Azeredo-Coutinho et al, 2016).…”
Section: Introductionmentioning
confidence: 77%
“…infection. However, another study demonstrated that early introduction of anti-helminthic therapy did not improve clinical outcomes in patients co-infected with helminths and L. braziliensis (Newlove et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…17 Sb-unresponsive CL is being seen clinically in the sense that recent cure rates of New World L. (Viannia) CL treated with systemic Sb are surprisingly low for a standard therapy, approximately 50-75%. [18][19][20][21][22] An undecided issue is whether there is a correlation between in vitro and clinical data, whether parasite resistance is the cause of clinical unresponsiveness. For Leishmania tropica from Iran, the mean effective dose (ED50) for parasites from 165 lesions that responded to systemic or ILSb was 4.6 μg/mL, whereas the mean ED50 for parasites from 16 lesions that did not respond was 19 μg/mL.…”
Section: 15mentioning
confidence: 99%